Relevance of a Hypersaline Sodium-Rich Naturally Sparkling Mineral Water to the Protection against Metabolic Syndrome Induction in Fructose-Fed Sprague-Dawley Rats: A Biochemical, Metabolic, and Redox Approach - Cidália Dionísio Pereira; Milton Severo; João Ricardo Araújo; João Tiago Guimarães; Diogo Pestana; Alejandro Santos; Rita Ferreira; António Ascensão; José Magalhães; Isabel Azevedo; Rosário Monteiro; Maria João Martins (International Journal of Endocrinology, 2014)
The Metabolic Syndrome increases the risk for atherosclerotic cardiovascular disease and type 2 Diabetes Mellitus. Increased fructose consumption and/or mineral deficiency have been associated with Metabolic Syndrome development. This study aimed to investigate the effects of 8 weeks consumption of a hypersaline sodium-rich naturally sparkling mineral water on 10% fructose-fed Sprague-Dawley rats (Metabolic Syndrome animal model). The ingestion of the mineral water (rich in sodium bicarbonate and with higher potassium, calcium, and magnesium content than the tap water used as control) reduced/prevented not only the fructose-induced increase of heart rate, plasma triacylglycerols, insulin and leptin levels, hepatic catalase activity, and organ weight to body weight ratios (for liver and both kidneys) but also the decrease of hepatic glutathione peroxidase activity and oxidized glutathione content. This mineral-rich water seems to have potential to prevent Metabolic Syndrome induction by fructose. We hypothesize that its regular intake in the context of modern diets, which have a general acidic character interfering with mineral homeostasis and are poor in micronutrients, namely potassium, calcium, and magnesium, could add surplus value and attenuate imbalances, thus contributing to metabolic and redox health and, consequently, decreasing the risk for atherosclerotic cardiovascular disease.